The First Amendment Doctrine of Underbreadth - William E. Lee (Washington University Law Quarterly, 1993)
This Article explains why the Supreme Court approaches differential treatment in such diverse ways. Because the topic of differential treatment of categories of expression has been explored elsewhere, this Article primarily focuses on differential treatment of communicators. In addition, because the press is frequently singled out for special treatment, the author discusses the question whether the press should be regarded as special. This Article argues that there are powerful reasons for preventing the government from discriminating among members of the press. These reasons also require that the government not discriminate between the press and nonpress communicators.
Keywords: Freedom of speech; Freedom of the press